Ph Control System Analysis Hydroponic Plants Smart Vertical In Agriculture - Wardani P K; Vandika A Y (Bandar Lampung University (UBL), 2017)
Indonesia is a country that most people farming his work as a farmer, but on the other hand that there is land in urban areas is already diminishing because a lot of the construction of buildings, malls, factories and as her even more public demand for vegetables from year to year has increased drastically and the solution to this problem is with a hydroponic system.Hydroponics is growing plants and growing techniques that utilize water instead of soil by emphasizing the need nutrients,temperature and pH for plants. Needs of hydroponic water at less than the plant with soil media, so is suitable for areas that have water supply and limited land. (https://id.wikipedia.org/wiki/Hidroponik) History Hydroponic growth in 1963 was born a term Hydroponics, a term given by someoneagronomy from the University of California, United States. beginning of activities to cultivate plants without soil media. Beginning of hydroponics experiment originated from research work in plant physiology laboratory testing using water fished. These systems use a lot of water as a growing medium that many people regard these media as aquaculture (Farming in the water). In the historical record how hydroponics has been around since thousands of years ago, for example, described in Babylon existing hydroponic hanging plants and floating plants in the region of china.In 1980,Indonesia began to develop hydroponics.